Rare association of central pontine myelinolysis with infantile tremor syndrome - Datta, Kalpana (Medknow Publications & Media Pvt Ltd, 2012)
Central pontine myelinolysis (CPM) is an acute demyelination within the central basis pontis. Though exact mechanism is not known it is seen commonly with rapid correction of hyponatremia and also with pontine ischemia or infarction, demyelinating diseases, pontine neoplasm and different metabolic diseases. We report a rare association of CPM in a patient of Infantile Tremor Syndrom (ITS). ITS is a syndrome of tremor, mental and physical retardation, pigmentary changes of hair and skin and anemia in malnourished children. Though first reported in Indian subcontinent many identical cases were reported from around the world. Our case is a 15 month old child with generalized tremor, mild hepatosplenomegaly with features of grade II malnutrition including skin and hair changes. All the signs and symtoms of tremor improved after treatment with the World Health Organization (WHO) protocol for protein energy malnutrition (PEM) and administration of propranolol without any side effects.